1H and 13C NMR spectroscopic studies of half-esters from monohydrolysis of dialkyl bicyclo[2.2.1]hept-5-ene-2, 3-dicarboxylates. Issue 3 (2004) - Hiraga Hiraga, Yoshikazu Yoshikazu; Niwayama Niwayama, Satomi Satomi
Abstract : The structures of the half-esters from the monohydrolysis of ( exo, exo )-, ( endo, endo )-, and ( endo, exo )-dialkyl bicyclo[2.2.1]hept-5-ene-2, 3-dicarboxylates were determined by 1 H and 13 C NMR as well as 2D NMR spectra, and the complete spectral assignment has been made. After conversion of one of the carboalkoxy groups to a carboxyl group, different tendencies were observed for the differences in 1 H and 13 C NMR chemical shifts between half-esters and the corresponding diesters.